43 Superheroes and sepsis 6 – quality improvement and leadership to improve patient care. (4th October 2017) - Rees, C; Fraser, C; Follett, R
Abstract : Background: An introduction to QI methodology and how it has driven system-wide change in the management of sepsis at GOSH. We explore the role of leadership and a multi-disciplinary approach to embed a standardised response and escalation in children with sepsis. Through sharing the tools and methods of engagement with staff, patients and families, we explore how learning from this case study can be applied to implementing organisation-wide improvement initiatives. Objectives: To share experience and learning to: 1. Apply Quality Improvement methodology to implementation of organisation-wide projects. 2. Understand the role of leadership in driving change across multi-disciplinary staff groups. 3. Take away ideas and methods for gaining widespread engagement in multidisciplinary teams to implement projects such as Sepsis 6. Involvement of patients and families: We have involved patients and families throughout the quality improvement project, shaping the training materials for staff and co-creating engagement materials for patients and families. Results: 6 months post-project launch: – Increase from 45% – 64% Sepsis 6 bundles completed in 1 hour trust-wide (International bundle compliance average 47%) – No unnecessary increase in use of broad-spectrum antibiotics trust-wide. – Increased confidence and empowerment of staff to recognise and treat sepsis. – Innovative tools and technology designed to support the recognition of the Septic child. – 1000 multidisciplinary staff trained in sepsis recognition and management. – Dashboards created to enable local improvements in all areas. Conclusions: Sepsis 6 has improved the recognition and management of paediatric inpatients in a tertiary hospital, with 65% of patients receiving the bundle within 1 hour. Leadership and quality improvement methodology are powerful tools to drive improvements in clinical services.